2005
DOI: 10.1002/app.22074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure on the morphology and spherulitic growth kinetics of polyolefin in‐reactor alloys

Abstract: Four polyolefin in-reactor alloys with different compositions and structures were prepared by sequential polymerization. All the alloys were fractionated into five fractions: a random copolymer of ethylene and propylene (25°C fraction), an ethylene-propylene segmented copolymer (90°C fraction), an ethylene homopolymer (110°C fraction), an ethylene-propylene block copolymer (120°C fraction), and a propylene homopolymer plus a minor ethylene homopolymer of high molecular weight (Ͼ120°C fraction). The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
3
2
0
Order By: Relevance
“…Similar phenomenon was observed isotactic PP/poly(ethylene‐ co ‐octene) (iPP/PEOc) in‐reactor alloys 56–58. So far, although there are some studies on crystallization kinetics of PP/EPR in‐reactor alloys,59–61 the effect of phase separation is seldom considered in this type of in‐reactor alloy. In our previous work, we reported the effect of phase separation in the melt on the linear spherulitic growth rate ( G ) of a PP/EPR in‐reactor alloy prepared by MSSP process 62.…”
Section: Introductionsupporting
confidence: 53%
“…Similar phenomenon was observed isotactic PP/poly(ethylene‐ co ‐octene) (iPP/PEOc) in‐reactor alloys 56–58. So far, although there are some studies on crystallization kinetics of PP/EPR in‐reactor alloys,59–61 the effect of phase separation is seldom considered in this type of in‐reactor alloy. In our previous work, we reported the effect of phase separation in the melt on the linear spherulitic growth rate ( G ) of a PP/EPR in‐reactor alloy prepared by MSSP process 62.…”
Section: Introductionsupporting
confidence: 53%
“…When dispersed phase is created in the copolymerization stage, each particle of dispersed phase is surrounded by some b‐ copolymers rich in PP produced acting as compatiblizing entities. Also, as particle size becomes smaller, the compatibility of the two phases increases, which is also in accordance with the findings reported by Xu et al,7 Jiang et al,9 and Li et al15…”
Section: Resultssupporting
confidence: 91%
“…When dispersed phase is created in the copolymerization stage, each particle of dispersed phase is surrounded by some b-copolymers rich in PP produced acting as compatiblizing entities. Also, as particle size becomes smaller, the compatibility of the two phases increases, which is also in accordance with the findings reported by Xu et al, 7 Jiang et al, 9 and Li et al 15 The rheological results match the 13 C NMR results shown in Figure 3. According to these results the higher interfacial adhesion between the two phases of EP5, revealed in the storage modulus and Cole-Cole graph, may be due to greater entanglements between the matrix and dispersed phase particles which are evident in 13 C NMR spectra.…”
Section: Rheologysupporting
confidence: 91%
See 1 more Smart Citation
“…According to Ryan, shear flow leads to stretching of the longest polyethylene chains, thus forming the “shish”, that nucleates crystallization of the lower molar-mass polyethylenes to afford the “kebab” . Several other groups have investigated shear-induced 1D crystallization and confirmed the prominent role of bimodal polyolefin MWDs. , Special injection molding processes, among them “shear-controlled orientation in injection molding” (SCORIM) , and “oscillating packing injection molding” (OPIM), , have been developed to fabricate all-polyolefin composites. Farah and Bretas used a slit die for polypropylene extrusion to prepare “all-polypropylene” composites with 2D self-reinforcement by shear-induced crystallization to form layered structures .…”
Section: Perspectives Of Multisite Olefin Polymerization Catalysismentioning
confidence: 99%